Real-world studies of crizotinib in patients with ROS1-positive non-small-cell lung cancer: experience from China - Hua Zhong; Jun Lu; Mengzhao Wang; Baohui Han (Journal of Comparative Effectiveness Research)
The treatment of non-small-cell lung cancer (NSCLC) has progressed from histology-oriented cytotoxic therapy to the era of molecular biology-oriented targeted therapy and immunotherapy. As the first tyrosine kinase inhibitor (TKI) targeting the ROS1 pathway, crizotinib is widely used as a first-line regimen for ROS1-rearranged NSCLC. However, due to the paucity of solid data from randomized, controlled phase III clinical studies, clinicians often require more systematic, real-world data-based guidance for its optimal clinical use. As one of the leading countries of real-world research on crizotinib, China has contributed significantly to data on standardization of the therapeutic use of crizotinib, including its clinical treatment patterns, the timing and duration of treatment and drug resistance monitoring and management.